2016
DOI: 10.18689/mjol-1000103
|View full text |Cite
|
Sign up to set email alerts
|

Middle Ear Risk Index [MERI] as Prognostic Factor in Tympanomastoidectomy with Tympanoplasty

Abstract: Aims: To evaluate a group of patients undergoing surgery for chronic otitis media with reference to the prognostic value of middle ear risk index and other factors in predicting the anatomical and functional outcome of tympanomastoidectomy with tympanoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
2
12
1
Order By: Relevance
“…An intact ossicular chain was seen in 50 patients (50%). This was in accordance with the observations of Mohammadi et al and Ahmed et al 12,13 However, several studies state that the presence of malleus handle is an important factor which affects the outcome. Hence defect of malleus is given a higher MERI score than defect of incus or stapes.…”
Section: Discussionsupporting
confidence: 92%
“…An intact ossicular chain was seen in 50 patients (50%). This was in accordance with the observations of Mohammadi et al and Ahmed et al 12,13 However, several studies state that the presence of malleus handle is an important factor which affects the outcome. Hence defect of malleus is given a higher MERI score than defect of incus or stapes.…”
Section: Discussionsupporting
confidence: 92%
“…Owing to its high prevalence rate, we do come across large number of cases and frequent undertaking of surgeries in order to clear the disease and restore the hearing is mandatory. 7 Trying to establish a uniform system to predict the outcome of surgery and counsel the patient accordingly plays an important role in country like India, especially where the cost of surgery and absence from work are major issues.…”
Section: Resultsmentioning
confidence: 99%
“…Aftab Ahmed et al also showed lower success rates with larger perforations, but the difference was not statistically significant (p= 0.35). 3 In 2001, MERI score was modified to include smoking as a risk factor. 3,7 According to our study, 11 (22%) cases were smokers while 39 (78%) were non-smokers with p value of 0.000.…”
Section: Discussionmentioning
confidence: 99%
“…The success of tympanoplasty is dependent on the surgical principle along with the pathological factors associated with disease. 3 There are a number of factors which influence the success rate of tympanoplasty such as age of the patient, size and site of the perforation, status of the ear (dry or discharging), ossicular status and the surgical technique, but their real role is still unclear. 4 Therefore, the success rate of tympanoplasty, as reported, can range from 35% to 92%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation